RADT-46. SYSTEMATIC REVIEW OF RADIOSENSITIZERS FOR MALIGNANT BRAIN TUMORS: POTENTIAL FOR LEARNING FROM PAST FAILURES. (9th November 2020) - Beg, Usman; Snyder, Brianna; Madhani, Sarosh; Hamidi, Nima; Mansouri, Alireza
Abstract: INTRODUCTION: Radiation therapy (RT) is the cornerstone of management of malignant CNS tumors but its efficacy is limited in hypoxic tumors. Although numerous radiosensitizer compounds have been developed to enhance the effect of RT, progress has been stagnant. Through this systematic review of the literature on radiosensitizers for malignant CNS tumors, we have sought to provide an overview of radiosensitizers developed to date, summarize their safety and efficacy, and evaluate areas for possible improvement. METHODS: PUBMED, EMBASE, Cochrane, and Web of Science were searched using terminology pertaining to radiosensitizers for brain tumor RT according to PRISMA guidelines. Publications reporting clinical evidence of non-antineoplastic radiosensitizers with RT for malignant CNS tumors were included. Pre-specified variables were extracted. Outcomes of interest were overall survival, progression-free survival, adverse events, and quality-of-life outcomes. RESULTS: Forty-eight publications were identified which included 20 unique non-antineoplastic radiosensitizing agents. Only 2/20 agents, fluosol with oxygen, and efaproxiral, showed improvement in outcomes in patients with glioblastoma and brain metastasis, respectively. A larger study was not able to confirm the latter. While molecular similarities between these two agents were not identifiable, the effective mechanism of action allowed them to modulate hypoxia from within blood vessels, without crossing blood-brain barrier. Nine agents required dose modification, change of schedule, or complete discontinuation due to toxicities. CONCLUSION: Despite decades of research, progress in the field of radiosensitizers for malignant CNS tumors has been limited. Available data demonstrates the lack of progress in identifying effective radiosensitizers for brain tumors. Of the many non-antineoplastic radiosensitizers that have been tested, only two have showed (limited) efficacy by targeting tumor oxygenation. Alternative strategies such as synthetic drug design, based on a mechanism of action that is independent of crossing the blood-brain barrier, may be necessary. Such studies are currently underway.